Controls on subaerial erosion rates in Antarctica - Marrero, Shasta; Hein, Andrew; Naylor, Mark; Shanks, Richard; Winter, Kate; Woodward, John; Dunning, Stuart; Westoby, Matt; Sugden, David (Earth and Planetary Science Letters, 2018)
Erosion rates offer insight on landscape development and the relative importance of chemical and physical processes of weathering. Minimal chemical weathering makes Antarctica an ideal location in which to compare the physical weathering of carbonate rocks to other lithologies. Here we report the first cosmogenic nuclide-derived erosion rates for carbonate rocks in Antarctica. Carbonate samples collected in the southernmost Ellsworth Mountains reflect a 36Cl erosion rate of 0.22 ± 0.02 mm/ka. This erosion rate is consistent with other reported Antarctic erosion rates, but is lower than 36Cl erosion rates derived from other arid regions in the world. These results are integrated with a continent-wide reanalysis of 28 erosion rate studies (>200 measurements), which comprise numerous rock types and other cosmogenic nuclides. By combining cosmogenic nuclide-derived erosion rates across studies, the larger trends provide insight into factors (e.g. lithology, glacial history, and availability of abrasive material) affecting subaerial erosion rates in Antarctica. Statistical analysis of the compiled data set shows differences based on lithology, with sandstone having the largest range of erosion rates. The compiled data also reveals higher erosion rates in areas with a large potential sediment supply, like the Dry Valleys. Samples collected from boulders yield lower erosion rates than those collected from bedrock, likely due to a combination of physical processes that affect boulders and bedrock differently, and glacial history, which can affect the apparent cosmogenic-nuclide derived erosion rate.